Intradural Spinal Lipoma of the Conus: A Case Report (Bangladesh Journal of Neurosurgery, 2019)
Intradural spinal lipomas are rare, and their origin is unknown. Although the clinical presentation may not be distinctive, patients usually present with neurological deficits secondary to mass effect. Total excision may not be possible all time, although subtotal resection is easily done by microsurgery. We report a case of intradural spinal lipoma of the conus medullaries. Total excision was done under microscope and histopathology proved lipoma.Bang. J Neurosurgery 2019; 8(2): 112-114